ANALISIS PERTUMBUHAN EKONOMI SEKTOR PERTANIAN, KEHUTANAN DAN PERIKANAN DI KABUPATEN KOTAWARINGIN TIMUR - Yudhi Crisvinus; Tri Yuliana Eka Sintha; Trisna Anggreini (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2018)
The purposes of this research is : Knowing Economic Growth of agriculture, forestry and fishery sector in East Kotawaringin Regency. The data used is Gross Regional Domestic Product in East Kotawaringin Regency and Central Kalimantan Province based on Current Prices and Constant Price 2010 in the year 2011 – 2015. The result is Growth Ratio Model analysis Province based on Current Prices in 2011-2015 sectors with positive connotation (++) : Food Crops Subsubsector and Agricultural Services and hunting. Sectors with negative connotation (+-) : Horticultural Crops and Plantation Crops Subsubsector. Analysis MRP Constant Price 2010, sectors with positive connotation (++) : Food Crops Subsubsector and Plantation Crops. Sectors with negative connotation (+-) : Horticultural Crops Subsubsector and Agricultural Services and hunting subsubsector, forestry and Logging subsector and Fisheries subsubsector.